Rancang Bangun Sistem Informasi Rekomendasi Produk pada Supermarket Menggunakan Content Based Filtering Berbasis Web - Muhammad Ridho Fasya; Muhamad Alda; Adnan Buyung Nasution (Yayasan Literasi Sains Indonesia, 2025)
The advancement of information technology drives transformation in the retail sector, including supermarkets. INDO BALI Supermarket in Tanjung Balai Karimun still relies on brochures for product promotion, which limits customer reach. This study aims to design and develop a web-based product recommendation system using the Content Based Filtering method. The system provides personalized recommendations based on product description similarity. Data processing includes tokenization, stopword removal, stemming, text normalization, TF-IDF calculation, and cosine similarity. The system was developed using PHP and MySQL with the waterfall method. Testing shows the system effectively delivers relevant product recommendations based on user preferences and supports improved promotional strategies and customer satisfaction.